2017
DOI: 10.3329/jbau.v14i2.32693
|View full text |Cite
|
Sign up to set email alerts
|

Clinically detection of foot and mouth disease at Kapasia upazila under Gazipur dristrict in Bangladesh

Abstract: Clinical detection of Foot and Mouth Disease in the cattle which study was carried out in Kapasia upazila under Gazipur district during from February 2011 to January 2012 and identifying the potential risk factors associated with the studies in Kapasia, Gazipur. A total of 315 infected cattle of different age, sex were examined in the upazila veterinary development center of Kapasia in Gazipur district. Total 86 (27.30%) cattle were infected with FMD on the basis of clinico-epidemiological determinants. The ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…The obtained results agreed with the previous findings of other authors (Alam et al, 2016;Mannan et al, 2009;Sarker et al, 2011;Rahman et al, 2015;Tomasula et al, 2007).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The obtained results agreed with the previous findings of other authors (Alam et al, 2016;Mannan et al, 2009;Sarker et al, 2011;Rahman et al, 2015;Tomasula et al, 2007).…”
Section: Discussionsupporting
confidence: 93%
“…FMDV infected animals up to 5 months to 1 year of age. This may be attributed to colostral antibodies which protect animals to 3 to 6 months of age which in turn decrease the rate of FMDV infection among calves of less than 6 months of age (Alam et al, 2016). However, most deaths were among animals less than 1 year ago.…”
Section: Discussionmentioning
confidence: 99%
“…Research and development in Bangladesh have developed effective CA practices for smallholder farms in the EGP using minimum soil disturbing implements mounted on 2WTs. The key outcomes are new knowledge developed on: (i) effective strip planting using the VMP [4][5][6]; (ii) planting machinery development and performance testing in the small fields using 2WTs [4,9]; (iii) agronomy for mechanised seeding with minimum soil disturbance and residue retention [5,6]; (iv) weed dynamics and weed management under CA [11][12][13][14][15][16]33]; (v) crop rotation effects on soils and weeds [33,34]; (vi) mechanised transplanting of NPT rice [24,25]; (vii) soil improvement under CA [17][18][19][20][21][22]; (viii) decreased greenhouse gas emissions under CA [23]; (ix) increased profit from CA-based SP + NPT rice in farmers' fields [8]; (x) water balance [27], which showed that wheat under CA (SP and increased residue retained) required 11-33% less irrigation water than the convention practices; and (xi) commercialisation models for sales of planters to LSP [31]. Based on the evidence presented, there should now be sufficient confidence for more widespread demonstrations across different agro-ecosystems in the EIP and for programmes to engage the private sector and farmers in adoption and out-scaling of CA for smallholder rice-based crop production in the EGP.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in SOC was equivalent to an additional 3.8-4.2 t of C ha −1 in the soils after five years under CA (SP for non-rice + NPT for rice with increased residue retention) (see Table 3 for the results at the Godagari, Rajshahi site). Soil N storage also increased with the CA practices, which also decreased soil bulk density and increased soil porosity [19]. Table 3.…”
Section: Benefit Of Ca For Soil Fertilitymentioning
confidence: 95%
See 1 more Smart Citation